2022
DOI: 10.21608/mjppf.2022.253069
|View full text |Cite
|
Sign up to set email alerts
|

Study of Combining Ability of Some Important Traits in Some Hybrid Rice Combinations

Abstract: The investigation was carried out at the experimental farm of Sakha Agricultural Research Station, Kafr El-Sheikh, Egypt, during 2018, 2019 and 2020 rice growing seasons. The aim of this study was to estimate the genetic statistics of the important traits in some hybrid rice combinations, 24 hybrids were produced by crossing six CMS lines with four testers and then evaluated in two seasons. Line x tester analysis showed highly significant difference in mean squares for genotypes of most traits. The best genoty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 6 publications
1
1
0
Order By: Relevance
“…(97.10, 95.80 and 95.90 %, respectively) in the first year, (95.70, 96.60 and 96.30 %, respectively) in the second year and (96.39, 96.22 and 96.11 %, respectively) for the combined data. These results agree with Elsharnobi et al (2022) they reported similar findings.…”
Section: Mean Performancesupporting
confidence: 93%
See 1 more Smart Citation
“…(97.10, 95.80 and 95.90 %, respectively) in the first year, (95.70, 96.60 and 96.30 %, respectively) in the second year and (96.39, 96.22 and 96.11 %, respectively) for the combined data. These results agree with Elsharnobi et al (2022) they reported similar findings.…”
Section: Mean Performancesupporting
confidence: 93%
“…Regarding number of filled grain panicle -1 the superior values resulted from hybrids, G46A×GZ6296 (209.0, 207.3 and 208.2 grains) in both seasons one and two and combined data, respectively and IR69625A×GZ6296 (195.3, 192.7 and 194.0 grains) in the first and second season and their combined data, respectively (Elsharnobi et al, 2022). (97.10, 95.80 and 95.90 %, respectively) in the first year, (95.70, 96.60 and 96.30 %, respectively) in the second year and (96.39, 96.22 and 96.11 %, respectively) for the combined data.…”
Section: Mean Performancementioning
confidence: 98%